Anthropisation et maladies à tique : l’exemple de la borréliose de Lyme - Boulanger, Nathalie (Comptes Rendus Biologies)
Ticks and tick-borne diseases are on the rise throughout the world. The reasons are multifactorial but all associated with human practices, including climate change and socio-economic and eco systemic changes. In the northern hemisphere, Lyme borreliosis and its vector, the tick belonging to the Ixodes ricinus complex, are particularly studied. Changes in forestry and the expansion of certain wild ungulates since the Second World War could explain the increasing presence of this tick in our environment. As it is likely to transmit other microorganisms potentially pathogenic to humans, an integrated multidisciplinary approach to identify human practices promoting its expansion is critical to control the (re)emergence of infectious diseases. Other ticks also benefit from the same anthropised context to increase their numbers in the environment.